2019
DOI: 10.3389/fpsyg.2019.01491
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and Implicit Affect and Judgment in Schizotypy

Abstract: Although emotion deficits in schizotypy have been reported, the exact nature of these deficits is now well understood. Specifically, for social anhedonia (SocAnh), there are questions about whether any decrease in positive affect only reflects an explicit bias not observed in other measures (e.g., implicit affect measure). At the same time, for individuals with elevated levels of perceptual aberrations or magical ideation (PerMag), there is some evidence of an increased influence of affect on judgment. It is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…At the same time, the mixed cluster had a trait PA level in between that of the negative and positive clusters. This is consistent with research showing negative schizotypy is associated with decreased PA while positive schizotypy is associated with similar levels of PA compared to control participants (e.g., Kerns, 2005;Martin et al, 2011Martin et al, , 2018. This is also somewhat consistent with a previous cluster analytic study that reported the mixed cluster had an intermediate level of openness to experience (Barrantes-Vidal et al, 2010), which is correlated with trait PA (e.g., r = .5; Işık and Üzbe, 2015), compared to a positive and negative cluster.…”
Section: Mixed Schizotypy Cluster Had the Greatest Emotional Impairmentssupporting
confidence: 90%
“…At the same time, the mixed cluster had a trait PA level in between that of the negative and positive clusters. This is consistent with research showing negative schizotypy is associated with decreased PA while positive schizotypy is associated with similar levels of PA compared to control participants (e.g., Kerns, 2005;Martin et al, 2011Martin et al, , 2018. This is also somewhat consistent with a previous cluster analytic study that reported the mixed cluster had an intermediate level of openness to experience (Barrantes-Vidal et al, 2010), which is correlated with trait PA (e.g., r = .5; Işık and Üzbe, 2015), compared to a positive and negative cluster.…”
Section: Mixed Schizotypy Cluster Had the Greatest Emotional Impairmentssupporting
confidence: 90%
“…For example, social anhedonia, which is characterized by diminished self-reported experience of positive emotion e.g. [10][11][12] , is associated with decreased self-reported attention to positive emotions 13,14 , as well as decreased influence of emotion on behavioral judgments 12,15 . This suggests that pleasant stimuli might have a reduced motivational salience for individuals with social anhedonia.…”
mentioning
confidence: 99%
“…Two new domains were identified: one defined as "Cognitive and behavioural disorganisation", which was created by merging the items of "Impulsive nonconformity" and "Cognitive disorganisation", showing that rather than divided they can be considered in a symbiotic relationship. Carrying out a proper assessment of environmental aspects such as relationships and the degree of pressure felt by the person on his or her behaviour, can make it possible to discriminate whether such thinking/tracking may also be due to a misinterpretation by the individual, highlighting emotional deficits in the schizotypal personality (Martin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%